Ready, set ... baby - Rusch, Elizabeth; Leng, Qin (Boston : Houghton Mifflin Harcourt, 2017)
Big kids Anna and Oliver give young readers the inside scoop on what to expect when a new baby is expected. In a fresh picture book/comic style, Ready, Set...Baby offers up a funny, loving, reassuring peek into life as a big brother or sister--with solid information, kid-friendly humor, and even tips for parents on how to help kids thrive when the new baby arrives.
Includes bibliographical references.
Keywords: Newborn infants -- Juvenile literature; Siblings -- Juvenile literature; Families -- Juvenile literature; Babies; Siblings; Families; Infants; Siblings